KARAKTERISTIK GELOMBANG DI BEBERAPA KAWASAN PERAIRAN SEKITAR SEMENANJUNG MINAHASA - Intanta Br Ginting; Ping Astony Angmalisang; Royke M Rampengan; Rignolda Djamaluddin; Hermanto WK Manengkey; Adnan S Wantasen (Sam Ratulangi University, 2021)
The waters surrounding the Minahasa Peninsula are important areas of various activities by use of coastal and marine space. This research aims, firstly to describe direction, period and height of waves at several water areas around the Minahasa Peninsula in various season. Secondly to analyze the characteristic of daily and seasonal waves. The wave parameter, which reanalysis by ECMWF for 5 years (September 2014 to august 2019) were used in this research. By the analysis spasial-temporal, the results are presented by the rose grapich waves direction and stock chart. The wave propagation in the north season and transition season I, is dominated by the northeasterly wave. While the wave propagation in the southern season and the transitional season II, is more diverse directions. The characteristics of the waves formed in the southeast Minahasa waters in the north season and transitional season I, show that the wave period is greater than in the waters of Manado Bay and Bitung waters. Furthermore, the wave characteristics formed in the waters of the Minahasa Peninsula show a significant wave height in Bitung waters which is higher than the waters of Manado Bay and Southeast Minahasa waters.Keywords: Waves, ECMWF, Minahasa Peninsula Waters Perairan sekitar Semenanjung Minahasa merupakan kawasan penting dalam berbagai aktivitas pemanfaatan ruang pantai dan laut. Penelitian ini bertujuan, pertama untuk mendeskripsikan arah, periode, dan tinggi gelombang di beberapa kawasan perairan sekitar Semenanjung Minahasa dalam berbagai musim yang berlangsung. Kedua adalah menganalisis karakteristik gelombang harian dan musiman pada perairan sekitar Semenanjung Minahasa. Data yang digunakan dalam penelitian adalah data reanalysis ECMWF (European Centre for Medium-Range Weather Forecasts) parameter gelombang selama 5 tahun mulai bulan September 2014 sampai Agustus 2019. Dengan metode analisis spasial-temporal hasilnya disajikan dalam bentuk grafik mawar arah datang gelombang dan grafik kotak (stock chart). Rambatan gelombang pada musim Utara dan musim Peralihan I, arah datangnya didominasi dari arah Timur Laut. Sedangkan rambatan gelombang pada musim Selatan dan musim Peralihan II, arah datangnya lebih beragam. Karakteristik gelombang yang terbentuk di perairan Minahasa Tenggara pada musim Utara dan musim Peralihan I memperlihatkan periode gelombangnya lebih besar dari pada perairan Teluk Manado dan Perairan Bitung. Selanjutnya karakteristik gelombang yang terbentuk di perairan Semenanjung Minahasa memperlihatkan tinggi gelombang signifikan di perairan Bitung lebih tinggi dari pada perairan Teluk Manado dan perairan Minahasa Tenggara.Kata kunci: Gelombang, ECMWF, Perairan Semenanjung Minahasa